The Pengaruh Profitabilitas, Ukuran Perusahaan dan Ukuran Kantor Akuntan Publik terhadap Audit Delay: Pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Halimah Eka Putri; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
This research aims to examine the effect of profitability, firm size, and KAP size on audit delay. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The research sample was determined using the purposive sampling method with a total sample of 29 companies. The data used is secondary data from the company's annual report. The analytical method used is multiple linear regression analysis. The results showed that the profitability had a negative effect on audit delay, the firm size had a positive effect on audit delay, while the KAP size did not affect on audit delay.